The importance of providing gender-affirming care in pharmacy practice - Lucille M. Abrams; Kevin Look; Lisa Imhoff (Elsevier, 2022)
Transgender and gender diverse (TGD) individuals face bias and discrimination across many health care settings including pharmacy. While there is evidence of successful interventions to increase provider awareness of the needs of TGD individuals in medicine, nursing, and social work, little work has been done by the pharmacy profession to recognize and meet the needs of this population. This commentary examines the gaps in pharmacy practice and pharmacy research with regards to the needs of TGD individuals and looks at allied health fields for potential solutions that can be adapted by the pharmacy profession.We first examine the social pressures that TGD individuals face in multiple social contexts and describe how bias and discrimination spill over into their interactions with providers and health care systems. Solutions for improving pharmacy practice research's ability to identify TGD individuals and their needs follows as a measure that will lead to solutions for improving pharmacy practice. A discussion of TGD individuals' responses to actual and perceived discrimination by pharmacists is discussed next, and why their avoidance of pharmacy care can be problematic to their health. The remainder of the paper focuses on how pharmacy education can train future pharmacists to provide inclusive care to TGD individuals, and how interprofessional education and continuing education can enhance future and practicing pharmacists' ability to provide high quality care to TGD individuals.